All the good parts - Nyhan, Loretta (Lake Union Publishing, 2016)
At thirty-nine, Leona Accorsi is broke, single, back in school, and living in her sister Carly's basement. She's perfectly content being quirky Auntie Lee to Carly's four children. That is, until Leona's doctor tells her that if she wants to have a child, she'd better do it now. Leona does want a baby. She always has, but the circumstances have never been right. Now she has a buge decision to make: face motherhood on her own or risk missing out on its rewards. Unfortunately, she's let her romantic life go stagnant. She barely even knows any single men. She has just a few prospects: a Vietnam vet and partial amputee, his intimidating son, the sweet but troubled man who tutors her niece, and a fellow nursing student she's never actually met. As Leona discovers more about each one, she realizes any of them could be the right man for the job. The more important question is, has she become the right woman?